(untitled) (International Seven Journal of Multidisciplinary, 2023)
The smoking epidemic is one of the greatest public health threats the world has ever faced. Smoking-related morbidity and mortality are a major public health challenge worldwide. Quitting smoking at any age is beneficial. The "O - Offer help to quit smoking" component of the MPOWER strategy is implemented through active smoking cessation clinics held at government health clinics in Malaysia. The National Smoking Cessation Program has set a target of achieving a smoking cessation rate of over 30% as a key performance indicator. Thus, smoking cessation clinic should be actively conducted in all government health clinics to ensure a good outcome of smoking cessation rate.